영화 <버킷리스트>를 통해 본 액티브 시니어와 웰다잉 고찰 - 강준수(Jun Soo Kang) (융합관광콘텐츠연구, 2023)
목적 본 연구의 목적은 노년의 신체 및 정신의 건강과 함께 죽음에 대한 준비를 통해서 효과적인 인생의 마무리가 지닌 중요성 인식을 제시하고자 하는 것이다. 방법 본 연구의 연구방법은 관련 문헌 연구와 함께 시니어의 삶을 묘사한 영화 <버킷리스트>의 핵심 장면 분석을 통해서 액티브 시니어 개념, 웰다잉의 필요성, 그리고 죽음의 수용과 긍정적 태도 인식의 측면에 대한 논의를 수행하고자 한다. 결과 액티브 시니어는 상호 소통이 이루어지는 노년기 친구가 필요하고 물질적 욕심보다는 인생을 되돌아볼 필요가 있다. 그리고 액티브 시니어는 인생의 좋은 마무리를 위해서 과거의 후회를 최소화하기 위한 노력의 일환으로 개인적 버킷리스트 실천을 통해서 남은 삶의 긍정성을 확보할 필요가 있다. 결론 현대사회의 액티브 시니어들은 적극적 참여 활동을 통해서 삶의 긍정성을 확보하면서 활기찬 인생을 살아갈 수 있고 행복한 죽음을 맞이할 가능성이 크다고 할 수 있다. 본 연구의 시사점은 액티브 시니어 특성과 웰다잉의 중요성 등을 관련 영화를 통해서 구체적으로 제시하고 있다는 점이다. 반면 본 연구의 한계점은 액티브 시니어와 관련된 논의를 특정 영화 매체에 한정하고 있다는 점이다. Purpose The purpose of this study is to present awareness of the importance of ending life effectively through preparation for death as well as physical and mental health in old age. Methods The research method of this study is to discuss the concept of active seniors, the need for well-dying, and aspects of acceptance of death and positive attitude recognition through analysis of key scenes from the movie <Bucket List> that depicts the lives of seniors along with research on related literature. Results Active seniors need friends in old age with whom they can communicate with each other and need to reflect on their lives rather than material greed. And in order to end life well, active seniors need to secure positivity for the rest of their lives by implementing their personal bucket list as part of their efforts to minimize past regrets. Conclusion It can be said that active seniors in modern society are able to live a vibrant life while securing positivity in life through active participation and are highly likely to die a happy death. The implications of this study are that the characteristics of active seniors and the importance of well-dying are presented in detail through related films. On the other hand, a limitation of this study is that discussions related to active seniors are limited to specific film media. KCI Citation Count: 0